Educational Tourism – Erasmus Case Study - Corina Larisa BUNGHEZ (Communications of International Proceedings, 2021)
Tourism is no longer just an activity for leisure, as the evolution and integration of niche forms of tourism into the mainstream industry is now a dynamic process that brings many new tourism forms into this sector. By intertwining tourism with education, we are now able to expand tourism activities in the sphere of learning and skill acquisition. Therefore, a most prolific form of tourism in our current global society is educational tourism. This form encompasses many diverse and complex activities that can enrich the knowledge of the participants and also serve as an instrument for direct and indirect economic development through what we can now categorize as a modern type tourism activity. This paper analyses the general characteristics of educational tourism and underlines the importance and the impact of this type of tourism. We present a case study on the Erasmus program, an education/tourism hybrid that has demonstrated that student and teacher mobility is a viable and profitable activity, benefiting both the participants and the higher learning institutions that collaborate in these endeavors. The resounding success of the Erasmus program can serve as a benchmark in future educational tourism projects because educational tourism represents a huge potential sector that will undeniably further expand in the future. Educational tourism works because its nature is perfectly representative of our current global society, in which mobility and ease of access are defining characteristics.
Keywords: tourism; education; Erasmus; mobility